Targeted Transgene Expression in Rice Using a Callus Strong Promoter for Selectable Marker Gene Control - Zhou, Jie; Li, Dongyue; Zheng, Chao; Xu, Rumeng; Zheng, Ersong; Yang, Yong; Chen, Yang; Yu, Chulang; Yan, Chengqi; Chen, Jianping; Wang, Xuming (Frontiers in Plant Science, 2020)
Precise expression of a transgene in the desired manner is important for plant genetic engineering and gene function deciphering, but it is a challenge to obtain specific transgene expression free from the interference of the constitutive promoters used to express the selectable marker gene, such as the Cauliflower mosaic virus (CaMV) 35S promoter. So, the solutions to avoid these inappropriate regulations are largely demanded. In this study, we report the characterization of a callus strong promoter (CSP1) in rice and its application for accurate transgene expression. Our results indicate that the high expression of the CSP1 promoter in the callus enables efficient selection of hygromycin equivalent to that provided by the CaMV 35S promoter, whereas its expression in other tissues is low. To evaluate possible leaky effects, the expression of a β-glucuronidase reporter driven by six specific promoters involving hormone signaling, pathogen response, cell fate determination, and proliferation was observed in transgenic rice plants generated by CSP1-mediated selection. Distinct β-glucuronidase expression was found consistently in most of the transgenic lines obtained for each promoter. In addition, we applied these specific marker lines to investigate the root cellular responses to exogenous cytokinin and auxin treatment. The results reveal that the root growth inhibition by cytokinin was differently regulated at high and low concentrations. In summary, we have established the feasibility of using callus-specific promoter-dependent selection to mitigate the transgene misexpression in rice. By enabling efficient transformation, rice plants with reliable transgene expression will be easily acquired for broad applications.